Acoustic absorption of passive destructive interference cavities. (June 2019) - Arjunan, Arun
Graphical abstract: Highlights: Sound absorption utilising the principles of passive acoustic interference. Design of interference cavities capable of cancellation at the cavity entrance. Polyamide-12 interference geometries using selective laser sintering. Influence of cavity diameter and shape on sound absorption coefficient is evaluated. Abstract: Acoustic products are primarily designed for broadband acoustic absorption. However, frequency-dependent acoustic absorption featuring passive design-based solutions are necessary to combat the growing noise pollution. Accordingly, this research investigates the targeted creation of sound absorption as a function of geometry utilising the principle of Acoustic Interference (AI). A methodology to design freeform geometries that can create targeted acoustic absorption is presented. The effectiveness of this methodology is then experimentally validated while quantifying the influence of length, diameter and geometry orientation. The results establish that AI has the potential to create 'near perfect' sound absorption that can be customised depending on the source frequency. The design freedom revealed by this study allows the exploitation of freeform geometries as passive high-efficiency sound absorbing devices.